Challenge with fumonisin FB1 + FB2 alters profile of fatty acids in Nile tilapia fingerlings - Lala, Bruno [UNESP]; Santos, Carolina Toledo [UNESP]; Roldi, Gabriel; de Oliveira Roça, Roberto [UNESP]; Seccatto Garcia, André Luiz; Gianeti, Thiago; da Silva Oliveira, Marivaldo; Braccini, Graciela; Andreola, Ricardo; Paolozzi, Rodrigo; Gasparino, Eliane; Grande, Paula Adriana; et al. (My University, 2020)
The toxicity of fumonisin (FB) has been proposed for different fish species because it causes imbalance between the sphingoid bases and impairs several cellular processes, such as cell differentiation and growth. In this study, we tested the hypothesis that FB changes performance and modifies the fatty acid profile in the muscle of Nile tilapia fingerlings. A total of 180 fish were distributed in four treatments: control treatment (without addition of FB), 20 (FB20), 40 (FB40) and 60 (FB60) mg/kg FB) in order to measure performance, muscle yield, mineral residue, protein, total lipids and fatty acid content. The apparent daily gain was lower (Y = 0.019x2-0.124x + 0.325; R2 = 0.928) for fish fed diets containing FB compared to the control group. The negative effect on growth rates resulted in a reduction in fillet yield (P < 0.001). Crude protein was statistically lower (FB60 = 15.38%) for the higher dose than for the control group (P = 0.0003). The moisture was higher for the FB20 level, with quadratic regression effect (R2 = 0.688), the ashes had a linear regression effect (R2 = 0.811) and showed a quadratic regression effect (R2 = 0.868). Total saturated fatty acids were higher in fish fed with FB60 (37.13 ± 0.99) diet than for any other treatment. Total monounsaturated fatty acids did not vary between dietary treatments, as did total omega 6 (ω6). Total omega 3 fatty acids (ω3) were significantly higher in fish fed with FB40 (4.99 ± 0.15) and FB60 (5.20 ± 0.13) diets than for FB20 (4.36 ± 0.03) and the control treatment (4.43 ± 0.18). Total polyunsaturated fatty acids were significantly higher in fish fed with FB40 (33.70 ± 1.01) and FB60 (33.73 ± 0.29) diets. Therefore, fumonisin worsens performance in Nile tilapia fingerlings and modifies their fatty acid profile, as it increases the amount of saturated and polyunsaturated fatty acids and decreases the level of monounsaturated fatty acids.
Keywords: Fusarium moniliforme; Lipidogenesis; Oreochromis niloticus; Toxicity